2020
DOI: 10.1002/advs.201903562
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR‐Net: A Recurrent Convolutional Network Quantifies CRISPR Off‐Target Activities with Mismatches and Indels

Abstract: The off‐target effects induced by guide RNAs in the CRISPR/Cas9 gene‐editing system have raised substantial concerns in recent years. Many in silico predictive models have been developed for predicting the off‐target activities; however, few are capable of predicting the off‐target activities with insertions or deletions between guide RNA and target DNA sequence pair. In order to fill this gap, a recurrent convolutional network named CRISPR‐Net is developed for scoring the gRNA‐target pairs with mismatches and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
86
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(87 citation statements)
references
References 41 publications
1
86
0
Order By: Relevance
“…Abadi et al proposed a machine learning-based method named CRISTA for CRISPR cleavage propensity prediction and found that DNA/RNA bulges are predictive features for boosting the performance [16] . Recently, a RNN-based CRISPR-Net has been developed to predict off-target activities with insertions and deletions from sgRNA-DNA pairs [27] . However, the improvement in the predictive power comes at the expense of training time due to the RNN-based model structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abadi et al proposed a machine learning-based method named CRISTA for CRISPR cleavage propensity prediction and found that DNA/RNA bulges are predictive features for boosting the performance [16] . Recently, a RNN-based CRISPR-Net has been developed to predict off-target activities with insertions and deletions from sgRNA-DNA pairs [27] . However, the improvement in the predictive power comes at the expense of training time due to the RNN-based model structure.…”
Section: Discussionmentioning
confidence: 99%
“…In CnnCrispr, bidirectional LSTM (BLSTM) [26] is also followed by CNN to predict off-target activity. CRISPR-Net utilizes RNN to quantify off-target activities with insertions or deletions between sgRNA and target DNA sequence pair [27] . Despite the progress made so far, there is still need for developing more accurate and interpretable methods for sgRNA on- and off-target activities prediction.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we adopted the Spearman correlation in log-scale for quantitative evaluations. We compared the performance of MOFF-target and MOFF-aggregate to 5 off-target prediction methods, including the benchmark CFD score 9 and its improved version Elevation 24 , two recent deep learning-based methods CNN_std 27 and CRISPR-Net 29 , and an energy-based model CRISPRoff 31 (Figures 4b-4c and Supplementary Tables 12-13). Among them, three machine learning-based methods (Elevation, CNN_std and CRISPR-Net) achieved good predictive power on their training dataset generated by GUIDE-seq, but the performances degraded when tested on datasets from the other two platforms, suggesting overfitting.…”
Section: Predicting Off-target Effect and Guide Specificity With Moffmentioning
confidence: 99%
“…Although experimental techniques are capable of quantifying Cas9 off-target activities, in silico prediction of the off-target effects remains the most efficient and cost-effective method for designing and optimizing CRISPR-based applications. The advancement of machine learning approaches has fueled the progressive improvement of off-target prediction over the past several years [24][25][26][27][28][29] . Moreover, biophysical modeling has provided new insights into the prediction of offtargeting from a bottom-up perspective [30][31][32] .…”
mentioning
confidence: 99%
See 1 more Smart Citation